Effect of Milling Process Variables on the Size of Hematite Ore Particles - Zahraa K. Baqer; Mohammed H. Hafiz; Firas F. Sayyid (Tikrit Journal of Engineering Sciences)
Hematite is one of the iron ores, and its chemical formula is (Fe2O3). The present research studies the hematite processing and the effect of grinding factors on it. Hematite ore is considered a low-grade iron ore due to its low iron percentage. The hematite comprised Fe (30.36%), Fe2O3 (43.41%), and other minerals, such as (CaO, SiO2, and Al2O3). It is essential to clean the valuable metal from impurities by making its closed components intertwined with impurities liberated through processing and grinding processes to increase its surface area, which is the research goal. The research methodology included collecting a sample of hematite ore from the Al-Hussainiyat area in (Anbar-Iraq). The hematite ore sample was crushed and ground. Then, samples were sieved using a vibrating sieve to analyze the raw particles based on their particle size distribution. Weight, time, and rotational speed were investigated to obtain the right balance between the input weight, grinding time, and mill speed to get the required particle size. The present research also aims to reduce the ore's particle size to less than 75 m and grind it to maximize its surface area. The findings of the milling process showed that the particle size reduced with increasing speed and duration. Also, it was found that the laboratory ball mill produced raw materials with a size of 20 microns and a maximum weight of 21.6 grams. These gains were achieved when a weight of 50 grams was added to 4 balls, a suitable number of balls, and the mixture was left inside for 30 minutes. The maximum weight achieved at 500 rpm for 10 minutes was 41 grams, with an internal weight of 100 grams and a particle size of 150 microns.